Reducing signal-to-noise ratio degradation due to coil coupling in a receiver array for 35Cl MRI at 9.4 T: A comparison of matching and decoupling strategies - Malzacher, Matthias; Hu, Ruomin; Chacón-Caldera, Jorge; Schad, Lothar R. (Concepts in magnetic resonance. Part B, Magnetic resonance engineering, 2018)
Next to conventional magnetic resonance imaging (MRI), which utilizes hydrogen nuclei, other nuclei, so-called X-nuclei, are of increasing interest since they can provide additional diagnostic information. However, X-nuclei MRI is challenging due to the lower Signal-to-Noise Ratio (SNR) compared to 1H (35Cl provides approximately 200 000 times lower SNR than 1H). In order to compete with this challenge, the use of high-field strengths and optimized hardware is crucial. In this work, a transmit-only receive-only (TORO) system for 35Cl MRI at a preclinical 9.4 T scanner is presented, composed of a volumetric birdcage coil and a 3 channel Rx array. SNR degradation despite preamplifier decoupling can no longer be neglected since the resonance frequency of 35Cl is low. This paper will prove the SNR degradation due to the coil coupling of the receiver coils for this setup and evaluate three different approaches to mitigate the SNR degradation. The performance of the different approaches is evaluated via single channel and combined SNR maps using phantom measurements. Finally, the SNR maps acquired with the Rx array are compared to the SNR map acquired using the Birdcage coil as a reference.
First published: 05 August 2018
Gesehen am 10.10.2019